2(x-5)-3=4x-2(5+x)

Simple and best practice solution for 2(x-5)-3=4x-2(5+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-5)-3=4x-2(5+x) equation:


Simplifying
2(x + -5) + -3 = 4x + -2(5 + x)

Reorder the terms:
2(-5 + x) + -3 = 4x + -2(5 + x)
(-5 * 2 + x * 2) + -3 = 4x + -2(5 + x)
(-10 + 2x) + -3 = 4x + -2(5 + x)

Reorder the terms:
-10 + -3 + 2x = 4x + -2(5 + x)

Combine like terms: -10 + -3 = -13
-13 + 2x = 4x + -2(5 + x)
-13 + 2x = 4x + (5 * -2 + x * -2)
-13 + 2x = 4x + (-10 + -2x)

Reorder the terms:
-13 + 2x = -10 + 4x + -2x

Combine like terms: 4x + -2x = 2x
-13 + 2x = -10 + 2x

Add '-2x' to each side of the equation.
-13 + 2x + -2x = -10 + 2x + -2x

Combine like terms: 2x + -2x = 0
-13 + 0 = -10 + 2x + -2x
-13 = -10 + 2x + -2x

Combine like terms: 2x + -2x = 0
-13 = -10 + 0
-13 = -10

Solving
-13 = -10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7x-6=6x+1 | | 3x+13=5x-27 | | z^3=13j | | -22+21=m-10 | | H=9x+4c-9+3x-8c+3 | | 9C=72WHATISC | | M=-8x+2z-6+3x-4z+3 | | 23(9+x)=-5(4-x) | | 6+2(16-1*6)= | | SolveT=M(3+FG)forG | | D=-2y+9x-9+4y-9x+6 | | x^2-7x+90=0 | | 1(2x-1)/33 | | (x^2+4)(x^2-1)=0 | | 3-2x=5-4x | | ln^2(x)=4x | | B=-3x+9y-5y+5x-4x+6y | | 12=4x+6 | | L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 | | A=-7y+6y | | 0.50x+0.25(30)=21.5 |

Equations solver categories